PICTORIAL VOCABULARY MODULE FOR VIRTUAL LEARNING AMONG LOWER SECONDARY ESL STUDENTS: Received: 10th March 2024 Revised: 29th April 2024, 30th April 2024 & 23rd May 2024 Accepted: 2nd April 2024 - Mohd Tahir, Mohd Haniff; Mokhtar, Mazlin Mohamed; Zaini, Muhamad Fadzllah; Mohd Ariff Albakri , Intan Safinas (PUPIL: International Journal of Teaching, Education and Learning, 2024)
English as a Second Language (ESL) students with limited vocabulary knowledge often face difficulties to learn and use English on a regular basis. To promote virtual learning, this study uses the module of pictorial vocabulary to help students learn vocabulary remotely. The module is tailored based on the ‘Substitution Augmentation Modification Redefinition’ (SAMR) Model. In this study, 150 ESL students from lower secondary schools across Malaysia use this module to help them learn the target words mentioned in the SBELC. A mixed methods research design is employed. After using the module, students have answered an evaluation form which is evaluated descriptively in terms of its mean scores and standard deviation. The qualitative data from the interview with the students are transcribed, categorized, and coded using content analysis. Based on the research findings, the students’ vocabulary knowledge has substantially increased after using the module. This study’s implications indicate that the use of pictorial vocabulary learning module is both interactive and effective in learning the target words. In the area of vocabulary acquisition, this research adds value as it can be used to carry out additional research to enhance the ability of students to learn new words.